Identification and characterisation of a regulatory region in the Toxoplasma gondii hsp70genomic locus(✩) - Ma, Yan Fen (2004)
Toxoplasma gondii is an important human and veterinary pathogen. The induction of bradyzoite development in vitro has been linked to temperature, pH, mitochondrial inhibitors, sodium arsenite and many of the other stressors associated with heat shock protein induction. Heat shock or stress induced activation of a set of heat shock protein genes, is characteristic of almost all eukaryotic and prokaryotic cells. Studies in other organisms indicate that heat shock proteins are developmentally regulated. We have established that increases in the expression of bag1/hsp30 and hsp70 are associated with bradyzoite development. The T. gondii hsp70 gene locus was cloned and sequenced. The regulatory regions of this gene were analysed by deletion analysis using β-galactosidase expression vectors transiently transfected into RH strain T. gondii. Expression was measured at pH 7.1 and 8.1 (i.e. pH shock) and compared to the expression obtained with similar constructs using BAG1 and SAG1 promoters. A pH-regulated region of the Tg-hsp70 gene locus was identified which has some similarities to heat shock elements described in other eukaryotic systems. Green fluorescent protein expression vectors driven by the Tg-hsp70 regulatory region were constructed and stably transfected into T. gondii. Expression of green fluorescent protein in these parasites was induced by pH shock in those lines carrying the Tg-hsp70 regulatory constructs. Gel shift analysis was carried out using oligomers corresponding to the pH-regulated region and a putative DNA binding protein was identified. These data support the identification of a pH responsive cis-regulatory element in the T. gondii hsp70 gene locus. A model of the interaction of hsp70 and small heat shock proteins (e.g. BAG1) in development is presented.